Altruism and the care of elderly parents: Evidence from Japanese families - Miki Kohara; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2006)
This paper analyzes what adult children would do for their parents were they frail and in need of long-term care. Focusing on the special case of parents' illness, the paper then investigates altruism in Japanese children. Descriptive statistics show that about 30% of adult children living separately from their parents provide long-term in-home care, which suggests that a significant number of Japanese children supply care. However, detailed examination reveals that this parental care is not motivated entirely by altruism. We show that children provide parental care when their parents are wealthy enough to meet the costs of nursing.
Keywords: D12; D13; J14; 330; Altruism; Informal Parental Care; Within-family Money and Time Transfers; Home Production; Familie; Eltern; Generationengerechtigkeit; Altruismus; Japan